Biomedical Applications of Zinc Oxide Nanomaterials - Zhang, Y.; R. Nayak, T.; Hong, H.; Cai, W. (Current Molecular Medicine, 2013)
Nanotechnology has witnessed tremendous advancement over the last several decades. Zinc oxide (ZnO), which can exhibit a wide variety of nanostructures, possesses unique semiconducting, optical, and piezoelectric properties hence has been investigated for a wide variety of applications. The most important features of ZnO nanomaterials are low toxicity and biodegradability. Zn2+ is an indispensable trace element for adults ( 10 mg of Zn2+ per day is recommended) and it is involved in various aspects of metabolism. Chemically, the surface of ZnO is rich in -OH groups, which can be readily functionalized by various surface decorating molecules. In this review article, we summarized the current status of the use of ZnO nanomaterials for biomedical applications, such as biomedical imaging (which includes fluorescence, magnetic resonance, positron emission tomography, as well as dual-modality imaging), drug delivery, gene delivery, and biosensing of a wide array of molecules of interest. Research in biomedical applications of ZnO nanomaterials will continue to flourish over the next decade, and much research effort will be needed to develop biocompatible/biodegradable ZnO nanoplatforms for potential clinical translation.
Keywords: drug delivery